1999
DOI: 10.1016/s0375-9474(99)85025-8
|View full text |Cite
|
Sign up to set email alerts
|

Physics of ultra-relativistic nuclear collisions with heavy beams at LHC energy

Abstract: We discuss current plans for experiments with ultra-relativistic nuclear collisions with heavy beams at LHC energy ( √ s = 5.5 TeV/nucleon pair). Emphasis will be placed on processes which are unique to the LHC program. They include event-by-event interferometry, complete spectroscopy of the Υ resonances, and open charm and open beauty measurements.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…It can be observed that our results are not very different to those of statistical models [10,80,81,82]. However, strangeness enhancement in our case has nothing to do with thermal and/or chemical equilibrium.…”
Section: Predictions For Rhic and Lhccontrasting
confidence: 54%
“…It can be observed that our results are not very different to those of statistical models [10,80,81,82]. However, strangeness enhancement in our case has nothing to do with thermal and/or chemical equilibrium.…”
Section: Predictions For Rhic and Lhccontrasting
confidence: 54%
“…The results discussed above allow a rather confident prediction for hadron ratios in central Pb-Pb collisions at LHC energy [96], presented in Table 3. The antiparticle/particle ratios are all very close to unity, with the exception ofp/p, reflecting the small, but nonzero, µ b value obtained from Eq.…”
Section: The Energy Dependence Of Hadron Ratiosmentioning
confidence: 87%